Exploring the Value of Islamic Law in the Context of Modern Education in Islamic Education Institutions - Nasrullah, Achmad Muzammil Alfan; Iqbal, Hafiz Atif (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This research explores Islamic legal values, including justice, equality, morality, and responsibility, in the context of modern educational management in educational institutions. The research employs a literature review approach using primary data sources such as Islamic law and educational management books and several secondary sources, including scholarly articles and related literature. This research indicates that exploring Islamic legal values (justice, equality, ethics, and responsibility) can shape a more moral working ecosystem in the management of educational organizations. These values serve as the foundation for realising managerial functions and decision-making processes.